Analisis Yuridis Rencana Penghapusan Sistem Outsourcing dalam Undang-Undang Cipta Kerja - Rahman, Muhammad; Hafis, Muhammad William; Saraswati, Putri (Sahabat Akademia Group, 2025)
This study discusses the regulation and legal impact of the outsourcing system in Indonesia in the context of Law Number 11 of 2020 concerning Job Creation and its derivative regulations, especially PP No. 35 of 2021. Outsourcing is a form of employment that allows companies to use labour from third parties. Although it can reduce costs and increase company efficiency, this system raises issues of protection of workers' rights. The focus of the study is directed at a legal review of changes in outsourcing regulations, as well as the implications of the government's plan to abolish them during Prabowo’s leadership. This study uses a normative legal method with a statute approach, and data is obtained through literature studies. The results of the study show that although the Job Creation Law provides flexibility for outsourcing practices, its implementation often creates job uncertainty, weak protection for workers, and potential violations of labour rights. The plan to abolish the outsourcing system has sparked debate between labour and employer groups, given the significant legal and socio-economic impacts. Therefore, fair and balanced implementation regulations are needed so that worker protection is maintained without hampering the national investment climate.